Padronização de modelo experimental de artrite na articulação temporomandibular induzida por zymozan em ratos e estudo do papel do óxido nítrico - Chaves, Hellíada Vasconcelos (2006)
Temproromandibular disfunction (TMD) is related to a masticatory system disfunction which can include the temporomandibular joint (TMJ), the masticatory muscles and/or other related structures. TMJ inflammatory disorders are one of the major pathology of TMD afecting a great number of patients. Although TMJ´s inflammation and pain are important cinical entities, their mechanisms are poorly understood. The purpose of the study is to propose an experimetnal model of TMJ´s arthritis to study its patophysiological mechanisms and inflammatory mediators such as nitric oxide (NO). Female Wistar rats (160-220 g) were used to the study. To induct TMJ´s arthritis, zymosan 40 microL (Zy: 0,25; 0,5; 1 ou 2 mg) was injected into left TMJ. The animals were sacrified in times 3 h, 6 h, 1, 2, 3, 5, 7, 10 e 21 days. Nitric oxide syntase inhibitors L-NAME (10, 30 e 100 mg/kg i.p.) or 1400W (0,5 e 1 mg/kg s.c.) were administered 30 min before TMJ´s arthritis induction. Leucocyte influx count in the sinovial fluid, vascular permability study using Evans blue dye extravasation, myeloperoxidase assay (MPO), NO production determination using Griess reaction, histopatological analyisis and imunohystochemical for induced NO synthase (iNOS) were utilized as parameters of this sutudy. It was observed that Zy (2 mg) induced significantly increase in leucocyte influx count (p<0,05), Evans blue dye´s extravasation (p<0,05), myeloperoxidase activity (p<0,05) and NO dosage (p<0,05) compared with control group 6 h after TMJ arthritis induction. Histopatological analysis of TMJ of Zy injected animals showed inflammatory cell infiltration in synovial membrane (SM), in conective periarticular tissue, in squeletic muscle tissue and thickness of SM in 6 h after TMJ arthritis. On the 10th day after TMJ arthritis, the TMJ remain showing leucocyte infiltration to synovial membrane (SM), to conective periarticular tissue, to squeletic muscle tissue and thickness of SM, as well as fibrosis of SM and articular disc. On the 21st d after TMJ arthritis, it was observed cell influx only to SM, showing, however, thickness of SM and the major fibrosis of SM, articular cartilage, conective periarticular tissue and articular disc. TMJ´s imunohistochemistry reaction for iNOS showed increase iNOS´s expression in animals with TMJ´s arthritis compared to the control group. L-NAME 100 mg/kg and 1400W 1 mg/kg reduced the increase in leucocyte count in the synovial fluid, the Evans blue dye extravasation, the histopatological alterations, and reduced the iNOS expression after imunohistochemistry reaction for iNOS 6 h after TMJ arthritis. These results sugest that this experimental model can be used to study TMJ arthritis, and that NO can participate in the physiopathological mechanisms of TMD.